Kedudukan Akta Hibah Tanah yang Melebihi Batas Maksimal bagi Penerima Hibah Beragama Islam - Rayyan Fakhri; Ilyas Ismail; Zainal Abidin (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2026)
Article 210 of the Compilation of Islamic Law (KHI) limits gifts to a maximum of one-third of the donor’s assets as a form of protection for the rights of heirs and to uphold social justice. However, in practice, land gift deeds drawn up by PPATs/PPATSs are still found to exceed this limit, thereby giving rise to controversy and legal disputes in the form of lawsuits seeking the annulment of such deeds in court. This phenomenon indicates a disconnect between legal principles and practical implementation, leading to legal uncertainty. This study aims to analyze the legal status of land gift deeds that exceed the maximum limit, legal protection for bona fide donees, and the responsibility of PPATs in their drafting. The research method employed is a normative legal approach using legislative, conceptual, and case-based analyses, along with primary, secondary, and tertiary legal sources analyzed qualitatively. The results indicate that a land grant deed exceeding the maximum limit retains limited legal validity, specifically only for the portions compliant with the provisions of the KHI. Legal protection for the grantee can be guaranteed if there is consent from all heirs. Furthermore, the PPAT bears civil, criminal, administrative, and ethical responsibilities regarding the deed drafted. Therefore, strengthening regulations, enhancing public legal literacy, and ensuring the PPAT’s due diligence are necessary to guarantee legal certainty and reduce disputes.